Corynebacterium Species Inhibit Streptococcus pneumoniae Colonization and Infection of the Mouse Airway - Horn, Kadi J.; Jaberi Vivar, Alexander C.; Arenas, Vera; Andani, Sameer; Janoff, Edward N.; Clark, Sarah E. (Frontiers in Microbiology, 2022)
The stability and composition of the airway microbiome is an important determinant of respiratory health. Some airway bacteria are considered to be beneficial due to their potential to impede the acquisition and persistence of opportunistic bacterial pathogens such as Streptococcus pneumoniae. Among these organisms, the presence of Corynebacterium species correlates with reduced S. pneumoniae in both adults and children, in whom Corynebacterium abundance is predictive of S. pneumoniae infection risk. Previously, Corynebacterium accolens was shown to express a lipase which cleaves host lipids, resulting in the production of fatty acids that inhibit growth of S. pneumoniae in vitro. However, it was unclear whether this mechanism contributes to Corynebacterium-S. pneumoniae interactions in vivo. To address this question, we developed a mouse model for Corynebacterium colonization in which colonization with either C. accolens or another species, Corynebacterium amycolatum, significantly reduced S. pneumoniae acquisition in the upper airway and infection in the lung. Moreover, the lungs of co-infected mice had reduced pro-inflammatory cytokines and inflammatory myeloid cells, indicating resolution of infection-associated inflammation. The inhibitory effect of C. accolens on S. pneumoniae in vivo was mediated by lipase-dependent and independent effects, indicating that both this and other bacterial factors contribute to Corynebacterium-mediated protection in the airway. We also identified a previously uncharacterized bacterial lipase in C. amycolatum that is required for inhibition of S. pneumoniae growth in vitro. Together, these findings demonstrate the protective potential of airway Corynebacterium species and establish a new model for investigating the impact of commensal microbiota, such as Corynebacterium, on maintaining respiratory health.